PENGARUH KREDIT KETAHANAN PANGAN DAN ENERGI (KKP-E) BRI TERHADAP KERAGAAN USAHATANI PADI SAWAH DI KABUPATEN PRINGSEWU - Ariantika, Devi; Ismono, R Hanung; Nugraha, Adia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
<!--[if gte mso 9]> <![endif]--><span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">This study aims to analyze the use of food security and energy credit (KKP-E) given by an Indonesian bank (BRI), the farming performance of farmer recipients and non recipients of the KKP-E, their income difference, the performance of farmer group members, and to determine farmer perceptions on the KKP-E. Th<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">is research used <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">survey<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN"> method<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">, with a total sample of 23 farmer recipients and 35 farmer non recipients of the KKP-E. This research was conducted in Pringsewu<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN"> Regency from<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> February to December 2014. <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">The d<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">ata w<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">as<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> analyzed descriptively<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">. <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">The results showed that majority of the farmers use<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">d<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> KKP-E with the use of over 90<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN"> percent. <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">There <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">was<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> significant difference on farming performance of the farmer recipients and non recipients of the KKP-E on the way of planting, obtaining seeds, using fertilizers, controling weed, using family labor and non family labor, production, and selling price of output. The income of the farmer recipients <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">wa<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">s greater than the income of non recipients of the KKP-E. Based on <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">their <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">productivity, the performance of the farmer recipients and non recipients <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">of <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">KKP-E <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">we<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">re on good categories.<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> Based on capacity, the performance of<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">the farmer recipients of KKP-E <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">wa<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">s on good category, while the farmer non recipients <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">were<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> not on good category. Most of the farmers ha<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">d<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> good perceptions of the KKP-E. <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">Key<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">words:<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">c<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">apital<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">, i<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">ncome<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">, <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">KKP-E, <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">p<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">erformanc<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">e<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> <![endif]--> This study aims to analyze the use of food security and energy credit (KKP-E) given by an Indonesian bank (BRI), the farming performance of farmer recipients and non recipients of the KKP-E, their income difference, the performance of farmer group members, and to determine farmer perceptions on the KKP-E. This research used survey method, with a total sample of 23 farmer recipients and 35 farmer non recipients of the KKP-E. This research was conducted in Pringsewu Regency from February to December 2014. The data was analyzed descriptively. The results showed that majority of the farmers used KKP-E with the use of over 90 percent. There was significant difference on farming performance of the farmer recipients and non recipients of the KKP-E on the way of planting, obtaining seeds, using fertilizers, controling weed, using family labor and non family labor, production, and selling price of output. The income of the farmer recipients was greater than the income of non recipients of the KKP-E. Based on their productivity, the performance of the farmer recipients and non recipients of KKP-E were on good categories. Based on capacity, the performance of the farmer recipients of KKP-E was on good category, while the farmer non recipients were not on good category. Most of the farmers had good perceptions of the KKP-E. <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">Key<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">words:<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">c<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">apital<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">, i<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">ncome<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">, <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">KKP-E, <span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">p<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">erformanc<span style="font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">e<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="69" SemiHidden="false" UnhideWhenUsed="false" Name="Med